2020
DOI: 10.3390/ani10111947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Lysine Levels on Production Performance and Milk Composition of High-Producing Sows during Lactation

Abstract: Modern genotype sows require enhanced nutrition because of their larger body size and higher reproductive performance than 20 years ago. This study aimed to evaluate the effect of dietary Lys on the lactating of primiparous sows and the second lactating period to minimize sow body weight (BW) loss and maximize the survival rate of piglets and litter gain. A total of 160 primiparous Yorkshire sows were randomly allotted to one of four experimental lactation diets. Formulated to contain 0.84%, 0.94%, 1.04%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…According to Hojgaard et al [72], estimates of the dietary requirements of digestible standardized ileal Lys for lactating sows vary widely, from 27 to 70 g/d, or from 4.9 to 10.5 g/kg, because factors like genetics, age, litter size, appetite, and feed ingredients can all affect the dietary requirement for Lys [71,72]. Liu et al [73] affirmed that primiparous sows eat 10-15% less than multiparous ones, so the percentage of SID Lys consumed during lactation must be increased in the former compared to the latter. Administering adequate supplies of Lys during lactation allows those sows to maximize milk production and their reproductive yield [73].…”
Section: Diets Focused On Amino Acid Supplementationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Hojgaard et al [72], estimates of the dietary requirements of digestible standardized ileal Lys for lactating sows vary widely, from 27 to 70 g/d, or from 4.9 to 10.5 g/kg, because factors like genetics, age, litter size, appetite, and feed ingredients can all affect the dietary requirement for Lys [71,72]. Liu et al [73] affirmed that primiparous sows eat 10-15% less than multiparous ones, so the percentage of SID Lys consumed during lactation must be increased in the former compared to the latter. Administering adequate supplies of Lys during lactation allows those sows to maximize milk production and their reproductive yield [73].…”
Section: Diets Focused On Amino Acid Supplementationmentioning
confidence: 99%
“…Liu et al [73] affirmed that primiparous sows eat 10-15% less than multiparous ones, so the percentage of SID Lys consumed during lactation must be increased in the former compared to the latter. Administering adequate supplies of Lys during lactation allows those sows to maximize milk production and their reproductive yield [73]. It is also important to emphasize that a low ingestion of lysine during lactation can have a negative effect on the sow's metabolic balance, secretion of reproductive hormones, and the interval between weaning and estrus while, in contrast, a high Lys consumption can improve metabolic states in sows and increase total litter weight at birth and the weight of piglets at weaning [74].…”
Section: Diets Focused On Amino Acid Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing demand for pig production requires modern sows to have a higher reproductive performance and nutritional status [ 1 ]. However, the widespread use of lean-type pig breeds has led to a negative nutritional balance in sows before and after production, affecting their health status.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to multiparous sows, primiparous sows have a lower feed intake during gestation and lactation, and need to mobilize more body reserves to feed piglets [ 2 ]. The nutritional intake of primiparous sows during lactation cannot meet the needs of lactation, growth, and development, which will lead to the body being in a catabolic state, and affect the reproductive life, and the growth performance of piglets [ 1 , 3 ]. Previous studies have shown that the loss of body reserves during lactation in primiparous sows affects reproductive performance and piglet production performance [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%